PRAKTIK KONSTRUKSI JENDER DI MEDIA MASSA - Wahyuni, Lilik (LITERA, 2014)
The mass media is part of one of the class systems. Therefore, it becomes one of the domination system arenas, one of which is the patriarchal norm domination. Through the mass media, society carries out a symbolic contestation such as daily linguistic exchanges to construct gender. This study aims to explain: (1) verbal forms of gender construction, (2) dynamics of gender construction, and (3) gender trajectory in the mass media. The study employed the qualitative approach, discourse analysis, and Gadamer’s hermeneutics. Based on the analysis, the findings are as follows. First, verbal forms of gender construction in the mass media are represented by forms of diction and expression styles showing symbolic contestation between males and females. Second, in the mass media, there are dynamics of the maintenance and replacement of doksa. Third, the gender trajectory in the mass media includes ideological changes and divided awareness.